Research on Expressive Writing in Psychology: A Forty-year Bibliometric Analysis and Visualization of Current Status and Research Trends - Gao, Xiaojuan (Frontiers in Psychology, 2022)
This paper offers a systematic overview of global academic publications of studies on expressive writing in psychology to date. By using two visualization tools VOSviewer and CiteSpace, we analyzed 2313 articles on expressive writing from the Web of Science (WoS) Core Collection database of Thomson Reuters. This paper might be the first attempt at providing a visualized analysis of the existing expressive writing research. It discusses the results from the following four sub-studies: the descriptive analysis of general results based on publications, the reference analysis based on citations, the domain analysis based on co-occurrence keywords, and the evolution analysis based on bursts and timezone view. It is found that the application of expressive writing to minority ethnic groups might be one of the future research trends. The results of this bibliometric analysis can be used to enhance the researchers’ understanding of expressive writing research and provide insights into future research opportunities in this area.